Effect of Late Nitrogen Applications on Grain Filling in Corn - J. A. Fernandez; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2018)
In order to evaluate the effect of nitrogen (N) with late-season fertilizer applications in corn, grain yield and grain filling parameters were evaluated for three genotypes under three N levels. Hybrids with different release years (3394, 1990s; P1151, 2000s; and P1197, 2016) and contrasting N application scenarios (zero-N, N at flowering, and N two weeks after flowering) were evaluated in two studies (dryland and irrigated) at the Ashland Bottoms Research Farm, Manhattan, KS, 2017 season. Results showed that under N stress conditions, the absence of N fertilization in corn significantly reduced yields, by affecting both grain number (GN) and grain weight (GW). Regarding genotypes, a positive trend was found between the year of release of the hybrid and yields, with greater yields for the modern hybrid (i.e., 206 bu/a for P1197). In respect to the grain filling process, N fertilization significantly increased the grain filling duration (GFD), without changes in the grain filling rate (GFR). Consequently, increments in GW were more related to changes in GFD rather than on the GFR.
Keywords: Late N application; corn; grain filling; late-nitrogen application